A case of tension faecopneumothorax after delayed diagnosis of traumatic diaphragmatic hernia - Tien Yew Chern; Allan Kwok; Soni Putnis (Surgical Case Reports)
Abstract Background Traumatic diaphragmatic injuries from blunt or penetrating trauma are difficult to detect in the acute setting and, if missed, can result in significant morbidity and mortality in the future. We present a case demonstrating the natural progression of this resulting in faecopneumothorax, which is a rare but serious presentation. Case presentation A 22-year-old young man presented with left upper quadrant and chest pain, nausea, vomiting, and intermittent obstipation with a background of previous lower chest wall stabbings. Computed tomography demonstrated a diaphragmatic hernia containing the splenic flexure of the colon, but he declined treatment and self-discharged. He presented three more times with similar symptoms and self-discharged within a 2-week period and finally presented dyspnoeic and septic. Computed tomography demonstrated tension faecopneumothorax from the perforated colon. He was taken to theatres and found to have a 3-mm perforation at his splenic flexure and underwent a segmental resection of the affected colon, intrathoracic washout, and biological mesh repair of his diaphragmatic hernia. He remained alive and postoperative recovery was uneventful. Conclusions A review of the literature demonstrates the rarity of traumatic diaphragmatic injuries resulting in faecopneumothorax with only a few case reports in the last 50 years. We present a case demonstrating a natural progression of the condition and highlight the importance of having a high index of suspicion of diaphragmatic injuries in the trauma setting.